The The Variation on Speaking Anxiety in Presentation Based on Genders - Dimas Ramadhany; Dzul Rachman (Journal of English Language Learning, 2024)
The majority of educational institutions require their students to be present in class. This study aims to investigate the factors that influence speaking anxiety among English language education students during presentations. The study takes a qualitative descriptive technique, experiences. Purposive sampling is used to choose participants from the University of Muhammadiyah in East Kalimantan. Data are gathered via surveys, observations, and interviews. The Foreign Language Classroom Anxiety Scale (FLCAS) is used to assess anxiety. The study's goal is to learn more about how kids feel and manage speaking anxiety, which will have consequences for classroom practices and teacher interventions.